EMPOWERING HIGH SCHOOL TEACHERS THROUGH AI: A PRACTICAL TRAINING ON CHATGPT AND GEMINI FOR DIGITAL LESSON DESIGN - Urip, Sri Rejeki; Pudjitriherwanti, Anastasia; Wijaya, Ayudhia Ratna; Purnamasari, Dwi Candra; Mutiaraningrum, Ira (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service program was designed to address the low level of digital literacy among high school teachers, particularly in integrating Artificial Intelligence (AI) into teaching. Observations revealed that most teachers were unfamiliar with AI tools like ChatGPT and Gemini, making it difficult for them to adapt to technological changes in education. The main problem identified was the lack of practical knowledge on how to use AI to design interactive and meaningful learning materials. To solve this, a structured training program was conducted at MAN Temanggung, consisting of workshops, hands-on sessions, and task-based learning focused on prompt creation and digital lesson planning. The training empowered teachers to explore, implement, and evaluate AI tools in their classrooms. As a result, participants demonstrated increased confidence and competence in using AI to support their teaching. This program contributes to enhancing the quality of education and aligns with the goals of Sustainable Development Goal 4 (Quality Education).